El análisis existencial : ensayos / Luis Martín-Santos ; edición de José Lázaro - Lázaro, José (Lázaro Sánchez); Martín-Santos, Luis (1924-1964) (Colección Humanidades médicas; 16)
Bibliogr.: p.[273]-279. Índices